2014
DOI: 10.1016/j.bbi.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain-induced depressive-like behavior and hippocampal neurogenesis and plasticity are dependent on TNFR1 signaling

Abstract: Patients suffering from neuropathic pain have a higher incidence of mood disorders such as depression. Increased expression of tumor necrosis factor (TNF) has been reported in neuropathic pain and depressive-like conditions and most of the pro-inflammatory effects of TNF are mediated by the TNF receptor 1 (TNFR1). Here we sought to investigate: 1) the occurrence of depressive-like behavior in chronic neuropathic pain and the associated forms of hippocampal plasticity, and 2) the involvement of TNFR1-mediated T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 123 publications
3
99
0
Order By: Relevance
“…Other chronic pain models in animals have also observed similar anxiety-like behavior after migraine-induced pain and sciatic nerve injury (Robinson et al, 1988, Lipton et al, 2000, McWilliams et al, 2003, McWilliams et al, 2004, Dellarole et al, 2014). Of further note is that mice with TIC injury develop the anxiety-like behaviors by week 8 post-injury in each of the three tests.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Other chronic pain models in animals have also observed similar anxiety-like behavior after migraine-induced pain and sciatic nerve injury (Robinson et al, 1988, Lipton et al, 2000, McWilliams et al, 2003, McWilliams et al, 2004, Dellarole et al, 2014). Of further note is that mice with TIC injury develop the anxiety-like behaviors by week 8 post-injury in each of the three tests.…”
Section: Discussionmentioning
confidence: 63%
“…The “pain affect” has also been described as the squeal of other physical and psychological disorders such as anxiety and depression (McWilliams et al, 2003, McWilliams et al, 2004, Maletic and Raison, 2009, Dellarole et al, 2014). These comorbidities have been so prevalent that approximately half of all patients suffering from chronic pain are also described as suffered from anxiety and depression (Asmundson and Katz, 2009, Asmundson and Taylor, 2009, Robinson et al, 2009, Macianskyte et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Mice receiving sciatic nerve CCI to induce neuropathic pain developed depressive-like behavior 4 weeks following ligature placement that was associated with increased hippocampal TNF and impaired dentate gyrus neurogenesis dependent on TNF receptor-1 signaling (Dellarole et al, 2014). In addition to various harmful effects of cytokines on neurons, depression mediates the activation of resident brain macrophages including microglia, which contribute to the existing immune disruption by releasing more cytokines (Frank et al, 2007;Maletic et al, 2007).…”
Section: Proinflammatory Cytokine Tnf˛ In Pain and Depressionmentioning
confidence: 99%
“…They hypothesized that chronic neuropathic pain-induced depression might be dependent on hippocampal tumor necrosis factor (TNF) through TNF receptor 1 (TNFR1) and is associated with different forms of hippocampal changes such as reduced neurogenesis, neuronal plasticity, and myelin remodeling. Other neuroplastic changes such as reduced spine density and dendritic retraction, were also described in animal models of depression or pain [103]. Therefore, it can be stated, that neurodegeneration is the primary defect in the induction of depression and chronic pain cycle of intensification.…”
Section: Neurodegeneration As the Primary Defect In The Induction Of mentioning
confidence: 99%
“…Dellarole et al [103] showed a temporal relationship between neuropathic pain and the occurrence of depressive-like symptoms as well as structural neuroplastic and white matter impairments of the hippocampus. They hypothesized that chronic neuropathic pain-induced depression might be dependent on hippocampal tumor necrosis factor (TNF) through TNF receptor 1 (TNFR1) and is associated with different forms of hippocampal changes such as reduced neurogenesis, neuronal plasticity, and myelin remodeling.…”
Section: Neurodegeneration As the Primary Defect In The Induction Of mentioning
confidence: 99%